Socio-Emotional Readiness of Students on Distance Learning (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionThe onset of the COVID-19 pandemic prompted an unprecedented shift in the educational landscape, with physical schools closing and distance learning becoming the new norm. Union Christian College (UCC) swiftly transitioned to distance education to ensure continued learning. However, the socio-emotional readiness of students for this altered mode of learning remains a largely unexplored terrain. This study aims to assess students' perceived socio-emotional readiness for distance learning, providing insights to inform a proposed adjustment plan addressing this critical aspect. MethodEmploying a descriptive-correlation research design, this study collected data from 107 Junior High School students of UCC who were enrolled during the 2020-2021 academic year when the institution initially implemented a pure distance learning approach. A researcher-developed questionnaire was used to gather data. Demographic profiles were described using frequency counts, while activities undertaken during the pandemic were documented. Socio-emotional readiness was presented using weighted means. Pearson Product-Moment Correlation analysis was conducted to identify significant relationships between variables. Results and DiscussionThe study revealed that many respondents were in Grade 10 and had family members also studying at UCC. Most parents were college graduates, and the family's monthly net income ranged from P20,000.00 to P50,000.00. In preparation for distance learning, students reported engaging in activities such as having breakfast before class, rising early, praying, reviewing notes, and organizing their belongings. Parental involvement included allowing leisure time before classes and providing advice and encouragement. Notably, students felt that peers influenced their socio-emotional readiness through mutual support in academics, sharing experiences, and spending time together, even virtually.Concerning socio-emotional readiness, students generally displayed moderate preparedness, indicating they were positioned between feeling fully prepared for distance learning and grappling with uncertainties. While longing for the school environment and interactions with peers and teachers, participants also admitted to experiencing stress when participating in distance learning. Correlation analysis did not yield significant relationships between profile variables and socio-emotional readiness. Conclusion and Recommendations In conclusion, the study underscores the importance of addressing students' socio-emotional readiness to ensure successful distance learning experiences. Students should have the tools and support necessary to thrive emotionally and academically in this new educational landscape. To foster a supportive and resilient learning community, targeted programs, and interventions to enhance socio-emotional preparedness are recommended. By doing so, educational institutions can navigate the challenges of distance learning, ensuring students' holistic development and success.
Keywords: socio-emotional readiness; distance learning; new normal education